Migration policies and state control in Argentina: experiences of vulnerable bolivian women who cross the borders - Pizarro, Cynthia Alejandra (2015)
This paper analyzes the way in which migration policies impact in the trajectories of Bolivian women who live and work in the outskirts of the main cities of Argentina. It focuses on three cases representative of the experiences of women laborers who, coming from the poorest rural areas of Bolivia, crossed the international border when Argentine migration policy was very restrictive. It shows that symbolic and socio-economic borders keep on excluding them, as well as other labor migrants, within the Argentine territory even when the current Migration Law enacted in 2004 is more inclusive, since it grants human and social rights to the migrants. It highlights the way in which particular state control mechanisms operate nowadays both at the international border and within the Argentine territory, and analyses the difficulties that these women experience due to their positions of class, ethnic, gender, nationality and migratory status. It remarks that despite the changes in the immigration policy of Argentina, state policies keep on controlling labor migrations in accordance with the paradigm of the governance of migration. It also analyses the strategies that these women develop in order to sort out state control policies. Therefore, it considers that they are active agents even though they still have feelings of fear and trauma associated with the crossing of borders.